2009
DOI: 10.1021/jp9080614
|View full text |Cite
|
Sign up to set email alerts
|

Born−Oppenheimer ab Initio QM/MM Molecular Dynamics Simulations of the Hydrolysis Reaction Catalyzed by Protein Arginine Deiminase 4

Abstract: Protein Arginine Deiminase 4 (PAD4) catalyzes the citrullination of the peptidylarginine via two successive stages: deimination and hydrolysis. Herein, by employing state-of-the-art BornOppenheimer ab initio QM/MM molecular dynamics simulations with umbrella sampling method, we have characterized the catalytic mechanism of the hydrolysis reaction: first the nucleophilic attack of a water molecule to the C ζ of the thiouronium intermediate yields a stable tetrahedral intermediate, and then the S-C ζ bond breaks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 60 publications
1
35
0
Order By: Relevance
“…The significant difference between the calculated (6.7 kcal/mol) and measured free-energy activation energies argues strongly against the involvement of the deprotonated cysteine nucleophile. A neutral Cys residue in the resting state of ADI is also consistent with our earlier PAD4 study, in which the ionized active site repels the substrate 47. Interestingly, the nucleophilic addition barriers for both free and peptidyl arginines are almost the same in our theoretical calculations (20.9 and 21.3 kcal/mol for PAD4 and ADI).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The significant difference between the calculated (6.7 kcal/mol) and measured free-energy activation energies argues strongly against the involvement of the deprotonated cysteine nucleophile. A neutral Cys residue in the resting state of ADI is also consistent with our earlier PAD4 study, in which the ionized active site repels the substrate 47. Interestingly, the nucleophilic addition barriers for both free and peptidyl arginines are almost the same in our theoretical calculations (20.9 and 21.3 kcal/mol for PAD4 and ADI).…”
Section: Resultssupporting
confidence: 91%
“…Free-energy simulations, particularly those with an ab initio description of the QM region, are necessary to reach quantitatively reliable conclusions 41, 45. Such free-energy QM/MM studies have indeed been performed recently for the catalysis of another GMSF enzyme, PAD4 46-47. To this end, MD calculations indicated that the Michaelis complex with a neutral Cys nucleophile is more stable than that with a deprotonated Cys, and the former yielded a free energy of activation comparable to experimental data 46.…”
Section: Introductionmentioning
confidence: 99%
“…8,29,31 While the initial body of work focused on PAD4, mechanistic studies on PADs 1 and 3 have confirmed that they too proceed through a similar reverse protonation mechanism. 30 Although modeling QM/MM studies 33,34 have suggested that the nucleophilic species is the thiol form of Cys645, it is hard to reconcile this data with the inverse solvent isotope effect observed on k cat / K m with PAD4, as well as PADs 1 and 3. 29,31 Based on these mechanistic studies, as well as mechanistic studies with F-amidine, Cl-amidine, 2-fluoracetamidine, and 2-chloroacetamidine, which show bell shaped pH inactivation rate profiles, we recently proposed that inactivation by F-amidine, Cl-amidine, and 2-fluoroacetamidine occurs via the initial attack of the Cys645 thiolate on the amidinium carbon which results in the formation of a stable protonated tetrahedral intermediate that mimics the initial tetrahedral intermediate formed during substrate hydrolysis (Figure 2); His471 is the likely proton donor.…”
Section: Pad Structure and Mechanismmentioning
confidence: 99%
“…In this model, deprotonation of the core Cys occurs in concert with nucleophilic attack on the guanidine carbon. Computational studies with PAD4 have suggested that a protonated Cys is energetically more favorable than a Cys thiolate in the Michaelis complex [38,39]. In addition, the core Cys residue in AGAT is also proposed to be predominantly protonated in the resting state, possibly activated by Asp305 for attack [33].…”
Section: Pentein Catalysismentioning
confidence: 99%